A cleft care workshop for speech and language pathologists in resource-limited countries: The participants' experiences about cleft care in Uganda and satisfaction with the training effect. (July 2020) - Alighieri, Cassandra; Kissel, Imke; D'haeseleer, Evelien; Bruneel, Laura; Bettens, Kim; Sseremba, Daniel; Pype, Peter; Van Lierde, Kristiane
Abstract: Objectives: workshops and specialized training programs are often inaccessible for speech and language pathologists (SLPs) based in resource-limited countries given the lack of supply, the long travel distances and the excessive participation fees. To stimulate life-long learning opportunities for all, this study described and measured the effect of a free, two-day cleft care workshop for SLPs in Uganda. The workshop included different topics related to the assessment and treatment of children with a cleft of the palate with or without a cleft of the lip (CP ± L). Methods: The participants who presented during the two-day course were asked to complete a pre- and post-workshop questionnaire to evaluate their satisfaction. The pre-workshop form also included some questions concerning cleft care in Uganda. Both the pre- and post-workshop forms included three visual analogue scales to investigate the evolution of the participants' estimation of their knowledge regarding speech in patients with a CP ± L and to assess the changes in their self-confidence in the diagnosis and treatment of this population. Results: seventeen SLPs completed the pre- and post-workshop questionnaires. In general, the participants were highly satisfied with the different themes covered in the program. After the training course, the participants rated their general knowledge about CP ± L and their self-confidence in the diagnosis and treatment of children with a CP ± L significantly higher than before the workshop. Conclusion: the vast majority of the SLPs reported that cleft care was not easily accessible in Uganda. The most commonly reported obstacle for cleft care was a lack of knowledge about this matter in the SLPs themselves highlighting the importance of the organization of additional education opportunities. The participants reported a significantly higher level of self-confidence in diagnosing and treating children with a CP ± L after the workshop. The content of this workshop can form the basis for future learning opportunities for SLPs based in resource-limited countries.